2011
DOI: 10.1186/1559-0275-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in diabetic kidney are associated with increased O-GlcNAcylation of cytoskeletal proteins including α-actinin 4

Abstract: PurposeThe objective of the present study is to identify proteins that change in the extent of the modification with O-linked N-acetylglucosamine (O-GlcNAcylation) in the kidney from diabetic model Goto-Kakizaki (GK) rats, and to discuss the relation between O-GlcNAcylation and the pathological condition in diabetes.MethodsO-GlcNAcylated proteins were identified by two-dimensional gel electrophoresis, immunoblotting and peptide mass fingerprinting. The level of O-GlcNAcylation of these proteins was examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…We showed that glucose inside the LLC-PK1 cells increases O-GlcNAcylation, which is correlated with inhibition of albumin endocytosis, opening the possibility that this mechanism could be involved in albuminuria in the early stage of DN. In agreement, Akimoto et al (56) showed increased O-GlcNAcylation in specific PT cytoskeleton proteins in a T2DM animal model. Ji et al (57) suggested that abnormal O-GlcNAcylation of actin and tubulin alters their polymerization, reducing microtubule-dependent reabsorption mechanism in PT cells.…”
Section: Pkb O-glcnacylation In Megalin-mediated Albumin Endocytosissupporting
confidence: 73%
“…We showed that glucose inside the LLC-PK1 cells increases O-GlcNAcylation, which is correlated with inhibition of albumin endocytosis, opening the possibility that this mechanism could be involved in albuminuria in the early stage of DN. In agreement, Akimoto et al (56) showed increased O-GlcNAcylation in specific PT cytoskeleton proteins in a T2DM animal model. Ji et al (57) suggested that abnormal O-GlcNAcylation of actin and tubulin alters their polymerization, reducing microtubule-dependent reabsorption mechanism in PT cells.…”
Section: Pkb O-glcnacylation In Megalin-mediated Albumin Endocytosissupporting
confidence: 73%
“…Post‐translational modifications, such as O‐linked N‐ acetyl‐b‐D‐glucosamine modification, have been described as responsible for morphologic changes at both the glomerular and tubular levels in the diabetic kidney, and these modifications involve cytoskeletal proteins (39). Cyto‐ skeletal changes, in turn, would affect the barrier to protein filtration, as suggested by both in vitro studies under HG conditions (40) and in vivo studies in human DN (41).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ubiquitination in the organization of cytoskeletal proteins has been recently linked to the proteasome activity (37), whereas the role of Lys63 ubiquitination in the regulation of cellular adhesion and migration has been described only in tumor cells (38). Post-translational modifications, such as O-linked Nacetyl-b-D-glucosamine modification, have been described as responsible for morphologic changes at both the glomerular and tubular levels in the diabetic kidney, and these modifications involve cytoskeletal proteins (39). Cytoskeletal changes, in turn, would affect the barrier to protein filtration, as suggested by both in vitro studies under HG conditions (40) and in vivo studies in human DN (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although poorly understood, actin O-GlcNAcylation has been implicated in modulating cardiac [32] and skeletal [33] muscle contraction, in cardioprotection [34], and in tissue changes in diabetics [35], as has another glucose-mediated actin PTM, glycation (the non-enzymatic attachment of glucose to lysine residues). Notably, purified actin is susceptible to glycation, as is actin in diabetic patients and animal models [3639], where glucose decreases polymerization and lowers F-actin levels [3941].…”
Section: Glucose-mediated Modificationsmentioning
confidence: 99%